Novel Platform for Droplet Detection and Size Measurement Using Microstrip Transmission Lines - de Novais Schianti, Juliana; L C Serrano, Ariana; Orquiza de Carvalho, Daniel [UNESP]; A Penchel, Rafael [UNESP]; Mota Pinheiro, Julio; Gongora-Rubio, Mario R.; Pamplona Rehder, Gustavo (MDPI, 2019)
We propose a novel platform for detecting as well as measuring the size of individual droplets in microfluidic channels using microstrip transmission lines. The most outstanding feature of our platform is that, as opposed to previous related works, its design allows for the droplet to flow in a microfluidic channel fabricated between the top strip and the ground plane of a microstrip transmission line. This provides enhanced interaction of the electromagnetic field with the detected droplets. The proposed design allows us to measure droplet size directly from the phase of the microwave signal, without the need for a resonator. The platform is based on low temperature co-fired ceramic (LTCC), which makes it more compatible with Radiofrequency (RF) and microwave technology than platforms used in previous works. With this platform, we are able to measure droplets as small as 150 µm in radius. It is worth pointing out that our device could also be used for detection, counting and measurement of other microscopic objects.
Keywords: emulsion; microfluidics; microstrip transmission line